2010
DOI: 10.1086/651582
|View full text |Cite
|
Sign up to set email alerts
|

Thirty Meter Telescope Site Testing X: Precipitable Water Vapor

Abstract: The results of the characterization of precipitable water vapor in the atmospheric column carried out in the context of identifying potential sites for the deployment of the Thirty Meter Telescope (TMT) are presented. Prior to starting the dedicated field campaign to look for a suitable site for the TMT, candidate sites were selected based on a climatology report utilizing satellite data that considered water vapor as one of the study variables. These candidate sites are all of tropical or subtropical location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 33 publications
3
40
0
Order By: Relevance
“…A radiometer at 225 GHz is operating at the CSO 5 on Mauna Kea. PWV quartiles between 1997 and 2001 can be found in Otárola et al (2010) and Radford (2011), 1.08 mm (25%), 1.82 mm (50%), and 3.32 mm (75%). The difference with the satellite measurements is around 15-20% and can again be caused by variations between the periods 1997-2001 and 2008-2010.…”
Section: Iasi (Infrared Atmospheric Soundingmentioning
confidence: 97%
“…A radiometer at 225 GHz is operating at the CSO 5 on Mauna Kea. PWV quartiles between 1997 and 2001 can be found in Otárola et al (2010) and Radford (2011), 1.08 mm (25%), 1.82 mm (50%), and 3.32 mm (75%). The difference with the satellite measurements is around 15-20% and can again be caused by variations between the periods 1997-2001 and 2008-2010.…”
Section: Iasi (Infrared Atmospheric Soundingmentioning
confidence: 97%
“…For these reasons, such aerosol measurements at Mauna Loa have only been carried out during daytime, and usable data requires reasonably good weather conditions (no clouds). (Otárola et al 2010) from the atmospheric optical depth at 225 GHz data by the 225 GHz tipping radiometer at the Caltech Submillimeter Observatory (Peterson et al 2003). site is almost 1000 m higher than MLO, and the fact that the AERONET observations are carried out during day time make a point to point comparison difficult. Nevertheless, the general features of both distributions still can be compared with each other: the mean SN Ångström exponent (1.3 ± 1.4) is compatible with the one measured by AERONET (1.2 ± 0.9).…”
Section: Aerosol Comparisonmentioning
confidence: 99%
“…In order to check the consistency of our approach, we compare our water intensity measurement to the PWV amount at Mauna Kea. For that purpose, we used the optical depth at 225 GHz data from the Caltech Submillimeter Observatory (CSO, Peterson et al 2003) and the empirical formula from Otárola et al (2010) to compute the PWV at Mauna Kea during the SN observation campaign (cf. Fig.…”
Section: Aerosol Comparisonmentioning
confidence: 99%
“…The results of the study by Otárola et al (2010), spanning a period of 4 years from early 2004 until the end of 2007, confirmed that the OAN site is dry and exceptionally good for astronomy research. The data analysis shows that during winter, even though the SPM site is about 230 m lower in elevation than Armazones, it is drier than the Armazones site.…”
Section: Temperaturementioning
confidence: 63%